Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jso.25680
|View full text |Cite
|
Sign up to set email alerts
|

The role of three‐dimensional printing in the surgical management of breast cancer

Abstract: A patient‐specific 3‐dimensional printed model (3DPM) of a woman with breast cancer was created. Mastectomy was favored as BCS would necessitate significant breast size alteration due to the extent of disease. After review of the 3D printed model, the patient and surgeon agreed on breast‐conserving surgery. Use of patient‐specific 3DPM in the setting of breast cancer may aid patient decision making and surgical planning, leading to enhanced surgical and oncological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Prior studies have demonstrated the need to overcome gaps in knowledge that may lead to increased DC 23,27,29 . 3D‐BMs have been used in medicine for the creation of personalized anatomical models, surgical guides, and custom implants enhancing preoperative planning and intraoperative efficiency 12‐17,38‐42 . 3D‐printed personalized models have also been used to enhance patient‐physician communication and the consent process in various diseases 43‐46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated the need to overcome gaps in knowledge that may lead to increased DC 23,27,29 . 3D‐BMs have been used in medicine for the creation of personalized anatomical models, surgical guides, and custom implants enhancing preoperative planning and intraoperative efficiency 12‐17,38‐42 . 3D‐printed personalized models have also been used to enhance patient‐physician communication and the consent process in various diseases 43‐46 .…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies have reported how personalized 3D‐printed models facilitate a patient's understanding of anatomy and the goal of the proposed surgical management 12‐17 . A personalized 3D‐printed breast model (3D‐BM) is a physical representation of the findings identified in the patient's contrast‐enhanced breast magnetic resonance imaging (MRI) exam.…”
Section: Introductionmentioning
confidence: 99%
“…3D printed breast models have been used to in preoperative planning, simulation of multiple surgical techniques, and as phantoms for assessing imaging parameters for both MRI and x-ray based mammography [13][14][15][22][23][24][25][26]. Conceptually, 3D printed models are also feasible for US-guided procedural training, provided the printed material is adequate for proprioceptive simulation of real human tissue and image production.…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction: Breast reconstruction surgeriesinclude either implant-based or autologous ap reconstructions. In autologous ap reconstructions, 3D printed models have been shown to facilitate the intramuscular dissection of perforator vessels by depicting the course and trajectory of the subfascial vascular tree and allowing the surgeon to view the model from various vantage points 24,30,31 . Improved understanding of the course of perforators and perfusion characteristics may be useful in reducing the risk of fat necrosis, unintended vessel injury, and the need for secondary procedures 32 .…”
Section: Pubmed Search: ((3d Printing) and ( Brocystic Change)) Or ((...mentioning
confidence: 99%